O08.5 Should All Pregnant Women Be Screened For Chlamydial Infection as Recommended by CDC, or Only Those Younger Than 25 Years as Recommended by USPSTF?. (13th July 2013) - Tao, G; Hoover, K
Abstract : Background: In the United States, chlamydia screening has been recommended for pregnant women of all ages by CDC, and for pregnant women younger than 25 years by USPSTF. The benefits of chlamydia screening are highly dependent on chlamydia prevalence. Very limited evidence, such as age-specific positivity in pregnant women, has been available to support these recommendations. We analysed data from a large commercial laboratory corporation with a substantial share of the U.S. market, with testing in all 50 states, to estimate the positivity of chlamydia among pregnant women. Methods: Among all chlamydia tests performed at a woman's first pregnancy-related visit between June 2008 and July 2010, we estimated chlamydia positivity by age, then further stratified by insurance coverage and geographic region. Results: Of 600, 990 pregnant women aged 15–44 years, 61.9% had private insurance and 34.1% had Medicaid coverage; 60.8% resided in the South region; 43.4% were aged 15–24 years, 26.7% 25–29 years, and 19.1% 30–34 years. Chlamydia positivity significantly decreased by age (15–19 years: 10.3%; 20–24 years: 5.6%; 25–29 years: 1.9%; 30–34 years: 0.9%; and 35–44 years: 0.6%). The pattern of decreased age-specific positivity was similar among insurance and region subgroups. Conclusions: Our findings of age-specific positivity, derived from a very large number of tests among pregnant women in the United States, suggest that it is more effective to screen younger pregnant women than older ones. Harmonizing CDC and USPSTF recommendations for pregnant women could be explored by review of age-specific positivity data and estimates of prenatal adverse health outcomes caused by chlamydia (miscarriage, preterm birth, and infant mortality) in order to develop consensus regarding quantitative thresholds of these health outcomes.